Implementasi net neutrality di indonesia ditinjau dari undang-undang ite - Pamungkas, Satriyo Widhi (Jurnal Komunikasi Profesional, 2021)
The problem of net neutrality has become a debate in many countries where the regulation on the net neutrality policy confirms that internet providers or Internet Service Providers (ISPs) are not allowed to make distinctions or be discriminatory in the selection of internet applications or content to be used by consumers or users. The purpose of this research is to analyze the application of network neutrality from the perspective of Indonesian law which specifically examines critically the applicable Information and Electronic Transactions Law. This research method is descriptive qualitative. The results show that the implementation of Net Neutrality in terms of the Information and Electronic Transactions Law is still not optimal because there are still network restrictions that are applied to certain Internet Network Providers. The results also show that there is a need for amendments to the ITE Law related to the enforcement of legal protection with the principle of forming a prohibition against the actions of Internet Service Provider (ISP) business actors that can disrupt the business climate.